Exercise erformance is impaired during the midluteal phase of the menstrual cycle - Freemas, J. A.; Baranauskas, M. N.; Constantini, K.; Constantini, N.; Greenshields, J. T.; Mickleborough, T. D.; Raglin, J. S.; Schlader, Z. (Medicine & Science in Sports & Exercise, 2021)
Purpose: This study aimed to test the hypothesis that aerobic exercise performance is impaired in the midluteal (ML) compared with the midfollicular (MF) phase of the menstrual cycle. Methods: Twelve recreationally active eumenorrheic women (25 ± 6 yr) completed exercise sessions during the MF and the ML phases. Each session consisted of an 8-km cycling time trial that was preceded by 10 min of cycling performed at a constant power below and above gas exchange threshold. Heart rate, ventilation, and oxygen uptake were continuously measured. RPE and ratings of fatigue were assessed during the time trial using visual analog scales. Total mood disturbance was calculated from the POMS questionnaire administered before and 20 min postexercise. Results: Salivary progesterone concentration was 578 ± 515 pg·mL-1 higher in ML compared with MF phase (P < 0.01), whereas estradiol concentration did not differ between phases (167 ± 55 vs 206 ± 120 pg·mL-1, P = 0.31). Total mood disturbance before exercise was greater during the ML phase compared with the MF phase (P < 0.01), but this difference was abolished postexercise (P = 0.14). Mean power output was lower during the ML phase (115 ± 29 vs 125 ± 28 W, P < 0.01), which led to a slower time trial in the ML phase (18.3 ± 2.0 min) compared with the MF phase (17.8 ± 1.7 min, P = 0.03). Ratings of fatigue were greater during the ML phase from 2 to 8 km (P = 0.01), whereas no differences in RPE were observed. Heart rate (P = 0.85), minute ventilation (P = 0.53), and oxygen uptake (P = 0.32) did not differ between phases during the time trial. Conclusion: Aerobic exercise performance is worse in the ML phase compared with the MF phase in recreationally active women, which was accompanied by a more negative mood state preexercise and increased ratings of fatigue.